Thyroid hormone induces progression and invasiveness of squamous cell carcinomas by promoting a ZEB-1/E-cadherin switch - Caterina Miro (Nature Portfolio, 2019)
The invasion of epithelial tumours often depends on the epithelial-mesenchymal transition. Here, the authors report that intracellular activation of thyroid hormone by the D2 deiodinase enzyme promotes invasion and progression of squamous cell carcinoma by transcriptionally up-regulating ZEB-1.